DINIYYAH IN PUBLIC SCHOOLS: A MODEL OF ISLAMIC CURRICULUM IMPLEMENTATION IN MULTI RELIGIOUS SOCIETY IN BANDA ACEH-INDONESIA - Marzuki, Marzuki (Jurnal Ilmiah Peuradeun, 2016)
The implementation of Islamic law in Aceh is included education by organizing Islamic curriculum in each level of education. How is the implementation of the curriculum in a multi-religious society like Banda Aceh? Banda Aceh has implemented a model of Islamic education through Diniyyah which has been implemented in all public schools in Banda Aceh since 2011, started with elementary, junior and senior high school. The results showed that the implementation of Islamic curriculum in Banda Aceh through diniyyah been operating effectively and do not make the non-Muslim communities disrupted. The implementation of Islamic education through Diniyyah did not clash with the main curriculum because it was implemented in the afternoon. So, this should be one of the models of Islamic curriculum implementation in Indonesia, particularly in areas which Muslim is majority without denying the existence of minorities.